PESAN DAKWAH DALAM ANIMASI NUSSA OFFICIAL EPISODE ADAB MENGUAP DAN JANGAN TIDUR SETELAH SUBUH: ANALISIS SEMIOTIKA ROLAND BARTHES - Nashihin; Rizky Ayu Nigtiaz (AN-NASHIHA Journal of Broadcasting and Islamic Communication Studies, 2024)
Islam is a regligion that calls on its followers to carry out da’wah, one of the da’wah contained in the film nussa and rarra is da’wah in the form of animations, the nussa and rarra animations contain many preaching messages, one of which is in the episode adab yawning and not sleeping after dawn, by therefore, this research changes peoples’s thingking by analyzing the nussa and rarra animations. this research aims to find out what kind of message of preaching faith, sharia and morals contained in the animated film nussa in the episode of adab yawning and don’t sleep after dawn and to find out the meaning of denotation and connotation using Roland Barthes semiotic theory. this research uses descriptive qualitative research method. the researcher, using Roland Barthes semiotic analysis research approach, to dissect the meaning of denotation and connotation in the episode of adab yawning and not sleeping after dawn. Roland Barthes semiotic analysis which examines the signifier and signified of an object. the results of research on the animated film nussa, the episode of the adab of yawning and not sleeping after dawn, namely that the message of preaching the faith is depicted through dialogue between mother, nussa, and rarra. what speks about everything is the will of Allah which is a form of tawakal. apart from that, the message of syariah da’wah can be seen in the characters played by umma (mother) and rarra (nussa’s sister) who wear the hijab. and finnaly the message of moral preaching which is reflected in the dialogue of maintaining manners, apologizing and saying thank you.